ANALISIS STRUKTUR GEDUNG TAHAN GEMPA DENGAN METODE SISTEM GANDA (DUAL SYSTEM) - Hendra Hendra; Lio Varan Zulkarnaen; Indah Rosanti; Rona Ariyansyah (Construction and Material Journal, 2021)
Most parts of Indonesia are earthquake prone areas with medium and high intensity. In the process of constructing the building, it needs to pay attention to several aspects. One of it is the effect of the earthquake. Earthquakes always attack the joint structure so that the structure needs to be designed using the moment-bearing frame system method with the concept of strong columns and weak beams combined with shear walls, so that the building can muffle earthquake vibrations. The building of Lidra Hotel, located on Raya Sedau Street, Samudera Indah beach, Sungai Raya Kepulauan sub-District, Bengkayang Regency, West Kalimantan Province. The building consists of 17 floors with a height of 67 meters from the ground, reinforced concrete structure. Based on the results of the Standard Penetration Test, this building will be builded on medium ground (SD site class) and included in the Seismic Design Category (KDS) D, then the calculation of this building uses the Special Moment Resistant Frame System (SRPMK) combined with a shear wall, so it is called the Dual System Method. Earthquake load planning uses the 2017 Indonesia Earthquake Map using the spectrum response method according to SNI 1726-2019. Calculation of loading according to SNI 1727-2020 and PPPURG 1987, structural concrete requirements for buildings according to SNI 2847-2019, calculation of structural steel roof according to SNI 1729-2020. Based on the calculation of the roof some results were obtained the size of the column and the truss size IWF 148.100.6.9mm, CNP gording 150.50.20.3,2mm, 1 type of plate 130mm;  2 types of beams 350mm/700mm and 300mm/600mm;  4 types of columns, K1 1200mm x 600mm, K2 800mm x 800mm K3 1000mm x 500mm, and K4 700mm x 700mm;  1 type of shear wall 300mm;  ladder plate and balustrade 130mm; 4 types of foundation 3600mm x 3600mm x 700mm – spun pile 9 D 600mm;  1500mm x 1500mm x 400mm – spun pile 4 D 350mm;  3000mm x 3000mm x 500mm – spun pile 9 D 500mm;  7600mm x 5600mm x 1000mm – spun pile 12 – 800mm. Keywords: Building Structure, Earthquake Resistance, Dual System, Spectrum Response.